1993
DOI: 10.1104/pp.101.3.773
|View full text |Cite
|
Sign up to set email alerts
|

An Osmotic Stress Protein of Cyanobacteria Is Immunologically Related to Plant Dehydrins

Abstract: Dehydrins are a family of desiccation proteins that were identified originally in plants (T.J. Close, A.A. Kortt, P.M. Chandler [1989] Plant Mo1 Biol 13: 95-108; G. Calau, T.J. Close 119921 Plant Physiol 98: 1523-1525. Dehydrins are characterized by the consensus amino acid sequence domain EKKCIMDKIKEKLPG found at or near the carboxy terminus; the core of this domain (KIKEKLPC) may be repeated from one to many times within the complete polypeptide. Dehydrins generally accumulate in plants in response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 23 publications
(19 reference statements)
0
63
0
Order By: Relevance
“…[5]) as well as cyanobacteria [7]. A number of genes coding for these proteins have been identified in Arabidopsis thaliana [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[5]) as well as cyanobacteria [7]. A number of genes coding for these proteins have been identified in Arabidopsis thaliana [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Bartels et al, 1990). Preliminary experiments with lichens with an antibody against a dehydrin from maize seedlings (Close & Lammers, 1993) brought no evidence for a similar role of ABA for these organisms, but further investigations are needed. Smith, Hobson & Ellis (1987) raise the question of a possible involvement of ABA in regulating the symbiosis, Hartung & Gimmler (1994) propose a stress physiological role in respect to desiccation tolerance.…”
Section: mentioning
confidence: 99%
“…botanik.uni-wuerzburg.de synthesized ABA is readily released to its environment because of the high permeability of the fungal plasma membrane for ABA, Hartung & Gimmler (1994) suggested that ABA could be involved in stress resistance of lichens. They argued that ABA could be released from the mycobiont to the photobiont where desiccation related proteins could be formed (Close & Lammers, 1993).…”
Section: mentioning
confidence: 99%
“…Dehydrin-like proteins also accumulate in osmotically stressed cyanobacteria (Close and Lammers, 1993), indicating that they have been evolutionarily conserved. A nove1 property of some ABAresponsive proteins (Jacobsen and Shaw, 1989) and dehydrins (Close et al, 1989) is their heat stability, or their resistance to heat-induced coagulation.…”
mentioning
confidence: 99%